Analisis dan Perancangan Sistem Informasi Kepegawaian pada PT. Bungo Limbur - Effendy, Gama Mujur; Mardiani, Mardiani (Jurnal Teknologi Sistem Informasi, 2022)
Bungo Limbur is a company which engaged in processing palm oil, which currently has approximately 114 employees that are divided into several divisions. Currently, PT. Bungo Limbur is having difficulties in grouping, saving, and managing employee data that is considered inefficient. Due to related difficulties, employee information system at PT. Bungo Limbur is created with the purpose to help some departments in executing existing work procedures, such as gathering employees data in group, assignments, and several other procedures. Method used in the making of this system is the RUP method (Rational Unified Process), which is a development method that is executed repeatedly. The related system design is applied by using Visual Studio Code application, MySQL, and Laravel as a framework with PHP programming language. The created system is expected to help the company in managing employee data. Based on the questionnaire given to the company regarding the problems faced, the information system created is able to solve related problems. However, it is necessary to develop a system so that the information system created can provide more significant benefits.